2008
DOI: 10.1177/1077559507313462
|View full text |Cite
|
Sign up to set email alerts
|

Child Maltreatment and Substance Abuse Among U.S. Army Soldiers

Abstract: Although substance abuse has consistently been linked to child maltreatment, no study to date has described the extent of substance abuse among child maltreatment offenders within the military. Analysis of U.S. Army data on all substantiated incidents of parental child maltreatment committed between 2000 and 2004 by active duty soldiers found that 13% of offenders were noted to have been abusing alcohol or illicit drugs at the time of their child maltreatment incident. The odds of substance abuse were increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…One exception is Wolock, Sherman, Feldman, and Metzger (2001), who found that substance use remains a significant and unique contributor to variance in substantiation risk even when other family risk variables are controlled. In addition, other studies have found that not only is the presence of alcohol or drug use in the home a major risk factor, but intensity and frequency of use can be associated with severity of maltreatment (Gibbs et al, 2008). However, given the wealth of other research findings about co-occurring risk factors in homes where caregivers are active substance misusers, the number of studies examining specific substance misuse effects was astonishingly low.…”
Section: Not Discussedmentioning
confidence: 90%
See 3 more Smart Citations
“…One exception is Wolock, Sherman, Feldman, and Metzger (2001), who found that substance use remains a significant and unique contributor to variance in substantiation risk even when other family risk variables are controlled. In addition, other studies have found that not only is the presence of alcohol or drug use in the home a major risk factor, but intensity and frequency of use can be associated with severity of maltreatment (Gibbs et al, 2008). However, given the wealth of other research findings about co-occurring risk factors in homes where caregivers are active substance misusers, the number of studies examining specific substance misuse effects was astonishingly low.…”
Section: Not Discussedmentioning
confidence: 90%
“…Not surprising with the number of articles that focused on child maltreatment outcomes, a large number of articles also focused on implications for child welfare professionals. These findings highlight the need to increase access to evidence-based interventions (Berger, 2005), increase collaboration with other systems such as the military, which has had extensive experience with substance-using caregivers who have been child maltreatment perpetrators (Gibbs et al, 2008), and gain a better understanding of substance use within the context of the other risk factors of the home environment (Scannapieco & Connell-Carrick, 2007).…”
Section: Psychosocial and Behavioral Child Outcomesmentioning
confidence: 97%
See 2 more Smart Citations
“…Alcohol abuse was found to be a factor in 25% of incidents of intimate partner violence committed by married active duty Army soldiers (Martin et al, 2010). Substance abuse was less frequently associated with child maltreatment (Gibbs et al, 2008).…”
mentioning
confidence: 96%